The future & wonders of floating & living concretes / Hamidah Mohd Saman - Mohd Saman, Hamidah
This book addresses two (2) wonders of concrete: how concrete can be a floating material and how living things can survive in concrete to make it durable. Concrete can be a lightweight material by introducing an expanding agent and increasing its volume. The small bubbles uniformly entrapped reduce the weight of concrete up to a lower density than the density of water, making it floats. An in-house developed spread-sheet can produce a mix proportioning of lightweight concrete with designated density and compressive strength. Meanwhile, bacteria can be grown in the concrete opening (crack) if they are supplied with sufficient food, and the precipitation from the biomineralisation process fills up the fissures and cracks to prolong the service life of the concrete. Several ways are looked for to accelerate urease activity to promote the biomineralisation process, which leads to calcite formation that can fill up the cracks in new and existing concretes. Findings from experimental and field works are included in this book to demonstrate the performance with various formulations of lightweight concrete, namely foamed concrete and treatment of concrete crack using bacteria. It is not complete when discussing concrete without bringing up these two (2) issues: the environment and sustainability, and this book is unexceptional.